Methods and techniques for determining the gas content of coal seams in China: a mini-review - Demin Chen; Baohua Qu; Jinyao Zhang; Qingming Long; Rui Sun (Fuel Processing Technology)
Coal seam gas content is a critical parameter for characterizing coal reservoirs, offering essential insights for gas disaster prevention and coalbed methane resource exploitation. This mini-review systematically examines coal pore structures, methane occurrence mechanisms, adsorption-desorption dynamics, and factors affecting gas desorption in granular coal. Focusing on China's context, it evaluates current methods and technologies for gas content determination. The direct method, relying on in-situ sealed sampling and coal-crushing techniques, remains the predominant approach, with advancements in truth-preserving sampling enhancing accuracy. Indirect prediction models, integrating geological and desorption data, have emerged but face limitations due to China's heterogeneous coal seams, as most models are validated only in localized mining areas. Challenges persist in model portability and applicability across diverse geological settings. The review identifies key gaps, including insufficient theoretical underpinnings of gas transport mechanisms and technical constraints in high-precision in-situ measurements. Future directions emphasize advancing theoretical frameworks, refining indirect models through multi-regional validation, and developing portable, real-time in-situ technologies to improve reliability and scalability. Measurement techniques for coal seam gas content are evolving toward greater diversity, prioritizing enhanced theoretical frameworks and high-precision in-situ technologies as pivotal future advancements.